ANALISIS ISI PEMBERITAAN ISU KEBERAGAMAN DI REPUBLIKA.CO.ID (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2024)
This study examines the issue of diversity on Republika.co.id. The purpose of this research is to understand the content of news coverage on diversity issues and the objectivity of the reporting related to these issues. The researcher used descriptive quantitative research with content analysis methods. The population in this study includes all news related to diversity using the keywords diversity and pluralism on the online site Republika.co.id, totaling 70 news articles. This study did not use any specific sampling techniques, so the entire population was used as the sample for this research. Reliability testing results using Holstii's formula (2M/N1+N2) show a score above 70% in all categories, making the coding sheet reliable. The study's findings indicate that: 1) The most dominant theme related to diversity issues is inter-group diversity at 47.8%, followed by religious diversity at 42.1%, ethnic diversity at 5%, racial diversity at 2.86%, gender diversity at 0.7%, and other themes at 1.4%. 2) The dominant sub-themes are religion and tolerance at 55%, inclusive education issues at 10.7%, language and culture issues at 9.2%, social and economic issues at 6.4%, ethnic discrimination at 2.1%, gender inequality at 1.43%, other issues at 15%, and migrant and refugee rights issues were never reported. 3) The main sources of news were divided into eight categories, with public event interviews and meetings being the dominant sources at 37.1%, while statistical data was never used as a news source. 4) News sources included education observers at 17.8%, religious leaders at 8.5%, minority group representatives at 5%, diversity and inclusion experts at 2.1%, others at 66.4%, and zero percent for human rights activists, with 11 news articles having no sources. 5) Most news (97.14%) is objective, meeting criteria for truthfulness, informativeness, and relevance, showing Republika's commitment to providing accurate and neutral information. Although some news articles were less objective (2.86%), this indicates room for improvement in maintaining balanced reporting. The implications of this study can help raise awareness among media practitioners, especially at Republika, about better ways to cover and present diversity journalism in the news. It is hoped that Republika can bring positive changes in presenting more inclusive and representative news. Additionally, this research can serve as a foundation for developing or strengthening journalistic codes of ethics and objectivity that consider diversity in reporting.